Toward more efficient and stable bifunctional electrocatalysts for oxygen electrodes using FeCo2O4/carbon nanofiber prepared by electrospinning. (December 2020) - Alegre, C.; Busacca, C.; Di Blasi, A.; Di Blasi, O.; Aricò, A.S.; Antonucci, V.; Baglio, V.
Abstract: In the present work, an iron-cobaltite spinel supported on N-containing carbon nanofibers (CNFs) shows a remarkable activity for the oxygen evolution reaction (OER) in alkaline solution, with an overpotential (η10mAcm -2 ) of 130 mV, one of the lowest values in literature so far. This material is also an excellent catalyst for the oxygen reduction reaction (ORR), what leads to an extraordinary reversible behavior (ΔE = EOER – EORR= 480 mV), being an economic and easy scalable candidate for the air electrode of metal-air batteries or for electrochemical devices where the oxygen evolution or the oxygen reduction is involved. In the present research, Fe partially replaces Co atoms in the Co3 O4 spinel structure to obtain a more economically feasible material, leading to a FeCo2 O4 /CNF, by using an electrospinning preparation procedure previously adopted for the Co3 O4 /CNF synthesis. The substitution of iron in the Co3 O4 /CNF spinel entails an outstanding onset potential toward the OER of 1.36 V vs. reversible hydrogen electrode, which is 120 mV lower compared with the pure spinel (Co3 O4 /CNF). An optimal distribution of the FeCo2 O4 particles on the CNF surface, with 3-nm-size particles, allows exposing abundant active sites, mainly Co 3+ and Fe 3+, responsible for the enhanced activity toward the OER, and Fe-Nx moieties and N-sites (N-graphitic/pyridinic), more active for the ORR. Besides, FeCo2 O4 /CNF shows a well-developed porous structure, favoring the mass transfer, a parameter particularly important for the ORR. To assess the stability of the catalysts for rechargeable alkaline metal-air batteries, cycling operation and chronopotentiometric experiments are carried out, showing a stable potential for 24 h. Graphical abstract: Image 1 Highlights: Spinel-type FeCo2 O4 supported on electrospun carbon nanofibers (CNFs) is investigated for oxygen reduction reaction and oxygen evolution reaction (OER). An outstanding onset potential toward the OER of 1.36 V vs. reversible hydrogen electrode is observed. FeCo2 O4 /CNF shows a superior reversible behavior than state-of-the-art catalysts.